2017
DOI: 10.1097/md.0000000000006232
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cognitive and motor tasks on the walking speed of individuals with chronic stroke

Abstract: Walking speed is a measure of gait performance after a stroke and a predictor of community ambulatory competence. Although gait decrements during a cognitive or motor task after stroke are well-documented, the differential effects of motor and cognitive tasks on the comfortable and maximum walking speeds of individuals with chronic stroke have not been investigated. This study aimed to compare the effects of cognitive and motor tasks on the comfortable and maximum walking speeds of individuals with chronic str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
10
0
2
Order By: Relevance
“…One hundred and eighteen (118) full texts were read, and 98 articles did not meet the inclusion criteria. Twenty articles were therefore included in this systematic review Figure 1; (20,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Among these, 17 studies were considered for the first and second objectives, while 7 studies contributed to the third objective.…”
Section: Selection Of Articlesmentioning
confidence: 99%
See 3 more Smart Citations
“…One hundred and eighteen (118) full texts were read, and 98 articles did not meet the inclusion criteria. Twenty articles were therefore included in this systematic review Figure 1; (20,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). Among these, 17 studies were considered for the first and second objectives, while 7 studies contributed to the third objective.…”
Section: Selection Of Articlesmentioning
confidence: 99%
“…A diverse array of locomotor tasks was used in the selected studies including simple forward locomotion (25,28,31,(33)(34)(35)(36)(37)(38)40), walking with direction changes (24,26,27,29,30,32,38,41,42), and avoiding obstacles during walking (36,39). One study used a challenging locomotor task consisting of a 10-m walking test combining obstacles, tandem-walking paths, and stepping onto targets (20).…”
Section: Locomotor Tasks Description and Outcomesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, according to a cross-sectional study done in 2017, patients with chronic stroke showed that cognitive tasks had a more significant influence than the motor tasks when patients were assessed during the completion of the study requirement. In other words, patients with chronic stroke tend to prioritize task accuracy and completion over maintaining activity speed [ 20 ].…”
Section: Reviewmentioning
confidence: 99%